Metabolic responses and benefits of glucagon‐like peptide‐1 (GLP‐1) receptor ligands. (10th May 2021) - Tanday, Neil; Flatt, Peter R.; Irwin, Nigel
Abstract : Glucagon‐like peptide‐1 (GLP‐1) is an incretin hormone that has undergone a revolutionary turnaround from discovery to clinically approved therapeutic. Rapid progress in drug design and formulation has led from initial development of short‐ and long‐acting drugs suitable for daily or weekly parenteral administration, respectively, through to the most recent approval of an orally active GLP‐1 agent. The current review outlines the biological action profile of GLP‐1 including the various beneficial metabolic responses in pancreatic and extra‐pancreatic tissues, including the gastrointestinal tract, liver, bone and kidney as well as the reproductive cardiovascular and CNS. We then briefly consider clinically approved GLP‐1 receptor ligands and recent advances in this field. Given the sustained evolution in the area of GLP‐1 drug development and excellent safety profile, as well as the plethora of metabolic benefits, clinical approval for use in diseases beyond diabetes and obesity is very much conceivable. LINKED ARTICLES: This article is part of a themed issue on GLP1 receptor ligands (BJP 75th Anniversary). To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v179.4/issuetoc